Raw Mill Machine Effectiveness Measurement through the Total Productive Maintenance (TPM) Implementation - Shandy Satria Wangsa Putra; Berty Dwi Rahmawati (OPSI, 2022)
PT X is a cement manufacturer company that experienced a loss of production caused by the high value of downtime. Based on downtime data, the raw mill machine appears to have the most significant value in machine downtime. This study aims to measure the raw mill machine's effectiveness in applying Total Productive Maintenance (TPM). The method used in this research is Overall Equipment Effectiveness (OEE). This method measures engine effectiveness and loss factor analysis using the Six Big Losses method, as well as finding the root cause through a five why and cause and effect diagram to give the most suitable recommendations. The result of this study found that the average OEE value in 2021 was below the international OEE standard of 85%, which is 72% and 67% for Raw Mill Plant 9 and Raw Mill Plant 10, respectively. The low performance of Raw Mill Plant 9 and Raw Mill Plant 10 machines is a consequence of breakdown losses and reduced speed losses that had happened. The root causes were a lack of training for mechanics and no stock control for spare parts. The recommendations are to improve training programs and facilities and create a spare parts inventory management system.